2020
DOI: 10.1111/pin.12891
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of programmed cell death ligand 1 (clone SP142) in mediastinal composite lymphoma: A report of two cases

Abstract: Composite lymphoma is a well‐known diagnostic entity exhibiting the synchronous occurrence of two or more distinct types of lymphomas in the same specimen. Here we report two patients, a 14‐year‐old female (Case 1) and a 45‐year‐old male (Case 2), with mediastinal composite lymphoma, comprising nodular sclerosis classic Hodgkin lymphoma (NSCHL) and primary mediastinal large B‐cell lymphoma (PMBL). Both patients had a mediastinal mass, and manifested two different histologic components in the same biopsy, one c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…48,49 Among reported series, nPD-L1 expression was variable in PMBL with different PD-L1 clones and cohorts, ranging from 29% to 100%, 9,14,[50][51][52][53] suggesting the presence of nPD-L1-positive and -negative subgroups of this distinct lymphoma. Accordingly, among our Japanese patients, nPD-L1 expression was observed in 100% with mediastinal NSCHL (n = 7) and 18% with PMBL (n = 11), 54 the latter being similar (15%) to another Japanese series. 48 However, these rates may be lower than in Western populations, possibly because of the relative paucity (approximately one-third) of these mediastinal diseases in Asia.…”
Section: Grey-zone Lymphomasupporting
confidence: 74%
See 1 more Smart Citation
“…48,49 Among reported series, nPD-L1 expression was variable in PMBL with different PD-L1 clones and cohorts, ranging from 29% to 100%, 9,14,[50][51][52][53] suggesting the presence of nPD-L1-positive and -negative subgroups of this distinct lymphoma. Accordingly, among our Japanese patients, nPD-L1 expression was observed in 100% with mediastinal NSCHL (n = 7) and 18% with PMBL (n = 11), 54 the latter being similar (15%) to another Japanese series. 48 However, these rates may be lower than in Western populations, possibly because of the relative paucity (approximately one-third) of these mediastinal diseases in Asia.…”
Section: Grey-zone Lymphomasupporting
confidence: 74%
“…48 However, these rates may be lower than in Western populations, possibly because of the relative paucity (approximately one-third) of these mediastinal diseases in Asia. 55 We recently reported nPD-L1 expression and its correlation with pathological findings (i.e., anatomical position) in two cases of mediastinal composite lymphoma, one with nPD-L1-positive PMBL (Figure 2A, 2B) and the other with nPD-L1-negative PMBL components, 54 which may provide additional support to the assertion of the two distinct subtypes of PMBL being closer to and more distinct from CHL, respectively.…”
Section: Grey-zone Lymphomamentioning
confidence: 73%
“…Our group has demonstrated that PD-L1 expression was more frequently observed in CHL than PMBL (100% vs. 18%), when using clone SP142 [ 125 ]. Seven NSCHL cases were positive for PD-L1, while only two out of 11 PMBL were positive for PD-L1.…”
Section: Differential Diagnosis Of Hodgkin Lymphomasmentioning
confidence: 99%
“…Seven NSCHL cases were positive for PD-L1, while only two out of 11 PMBL were positive for PD-L1. Notably, these PD-L1-positive PMBL cases were accompanied by a relatively rich inflammatory background, with a moderate number of small lymphocytes, and/or sclerotic changes, with difficulties to differentiate from MGZL [ 125 ]. Using the same antibody clone, a study by the Lymphoma Study Association (LYSA) also showed that neoplastic PD-L1 expression was more frequently observed in CHL than in MGZL (80% vs. 54%) [ 126 ].…”
Section: Differential Diagnosis Of Hodgkin Lymphomasmentioning
confidence: 99%
“…CL is rarely described in literature, and its description has been limited to isolated case reports (9)(10)(11)(12). However, its incidence may be underestimated as sophisticated techniques are required in the diagnosis of CL, and, due to its inconsistent definitions, the incidence of CL reported across different studies varies (13).…”
Section: Literature Reviewmentioning
confidence: 99%